2007
DOI: 10.1111/j.1365-2354.2006.00757.x
|View full text |Cite
|
Sign up to set email alerts
|

Bone mineral status after treatment of malignant lymphoma in childhood and adolescence

Abstract: The relationship between bone mineral mass and cumulative dose of corticosteroids (CDC) was investigated in 42 children and adolescents treated for Hodgkin disease (HD; n = 22) and non-Hodgkin lymphoma (NHL; n = 20). The median age at the time of the study was 24.1 years for HD survivors and 14.1 years for NHL survivors. Dual-energy X-ray absorptiometry [bone mineral density of the lumbar spine (LS-BMD) expressed as Z-scores] and peripheral quantitative computed tomography at the distal radius [trabecular volu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
30
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 24 publications
2
30
0
1
Order By: Relevance
“…Nysom et al found a reduced BMD in patients over 11 years of treatment for malignant lymphoma, but the decreased BMD was associated with height loss during growth, and when adjusted for bone size, bone mass remained within normal range in this group [23]. Sala et al reported a study of 42 patients treated for lymphomas (22 of them had HD) showing a significant reduction in spine BMD (measured with DXA) and vBMD (based on CT examination) in the children who received over 5 g/m 2 of steroids compared to those who received less than 5 g/m 2 [24]. In our HD patients, no differences were found in either anthropometric traits or bone mass in relation to reference group.…”
Section: Discussionmentioning
confidence: 85%
“…Nysom et al found a reduced BMD in patients over 11 years of treatment for malignant lymphoma, but the decreased BMD was associated with height loss during growth, and when adjusted for bone size, bone mass remained within normal range in this group [23]. Sala et al reported a study of 42 patients treated for lymphomas (22 of them had HD) showing a significant reduction in spine BMD (measured with DXA) and vBMD (based on CT examination) in the children who received over 5 g/m 2 of steroids compared to those who received less than 5 g/m 2 [24]. In our HD patients, no differences were found in either anthropometric traits or bone mass in relation to reference group.…”
Section: Discussionmentioning
confidence: 85%
“…57,60 Reduction in LS aBMD and in trabecular bone at the wrist (assessed by pQCT) was identified in a large minority of survivors of malignant lymphomas and correlated significantly with the cumulative dose of corticosteroid administered. 61 Decreased Bone Mineral Density and Acute Lymphoblastic Leukemia (ALL)…”
Section: Bone Mineral Loss and Cancer In Early Lifementioning
confidence: 99%
“…Considering the mechanism by which steroids produce fractures, 104 it is curious that there is not more evidence in support of prior corticosteroid therapy contributing to osteopenia and/or osteoporosis in survivors, particularly when the range of cumulative doses is as wide as that reported by Nysom et al ). In survivors of ALL 74 and malignant lymphomas, 61 high cumulative doses are associated with reduced BMD. The paucity of such findings may reflect small sample sizes and confounding effects of other chemotherapy and cranial irradiation.…”
mentioning
confidence: 99%
“…Reduced BMD has been described in adolescent and adult NHL survivors after stem-cell transplantation [52] and in childhood NHL survivors after chemotherapy combined with cranial radiotherapy [9,29]. In our study, which is the largest cohort of long-term childhood NHL survivors, BMD TB and BMD LS were within the normal range.…”
Section: Discussionmentioning
confidence: 57%